Weighty problems : embodied inequality at a children's weight loss camp - Backstrom, Laura (Rutgers University Press, 2019)
Many parents, teachers, and doctors believe that childhood obesity is a social problem that needs to be solved. Yet, missing from debates over what caused the rise in childhood obesity and how to fix it are the children themselves. By investigating how contemporary cultural discourses of childhood obesity are experienced by children, Laura Backstrom illustrates how deeply fat stigma is internalized during the early socialization experiences of children. Weighty Problems details processes of embodied inequality: how the children came to recognize inequalities related to their body size, how they explained the causes of those differences, how they responded to micro-level injustices in their lives, and how their participation in a weight loss program impacted their developing self-image. The book finds that embodied inequality is constructed and negotiated through a number of interactional processes including resocialization, stigma management, social comparisons, and attribution.